2022
DOI: 10.1161/circgen.121.003605
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Clinician Perceptions of Precision Cardiology Care: Findings From the HeartCare Study

Abstract: BACKGROUND: Routine genome-wide screening for cardiovascular disease risk may inform clinical decision-making. However, little is known about whether clinicians and patients would find such testing useful or acceptable within the context of a genomics-enabled learning health system. METHODS: We conducted surveys with patients and their clinicians who were participating in the HeartCare Study, a precision cardiology care project that returned results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Literature on barriers to genetic testing in other disciplines including cancer and neurology exists at length. Previous research on the barriers to the use of genetic testing in the world of subspecialty cardiac care focused on the patient perception of genetic testing [27] and practitioners' confidence and desires for education in cardiovascular and sudden cardiac death genetics [28]. Past research has also demonstrated that there is no significant psychological harm done to patients who undergo cardiovascular genetic testing [29].…”
Section: Introductionmentioning
confidence: 99%
“…Literature on barriers to genetic testing in other disciplines including cancer and neurology exists at length. Previous research on the barriers to the use of genetic testing in the world of subspecialty cardiac care focused on the patient perception of genetic testing [27] and practitioners' confidence and desires for education in cardiovascular and sudden cardiac death genetics [28]. Past research has also demonstrated that there is no significant psychological harm done to patients who undergo cardiovascular genetic testing [29].…”
Section: Introductionmentioning
confidence: 99%